Morphological variation and genealogical discordance in Caatinga sand lizards Calyptommatus Rodrigues 1991 (Squamata: Gymnophthalmidae) with the description of a new species - Recoder, Renato Sousa; Marques-Souza, Sergio; Silva-Soares, Thiago; Ramiro, Carolina Nisa; Castro, Thiago Marcial; Rodrigues, Miguel Trefaut (Zootaxa, 2022)
In the last decades, a remarkable fauna of psammophilous and fossorial squamates was discovered in sandy habitats of the semiarid Caatinga of northeast Brazil. Despite the increasing accumulation of genetic data from this unique fauna, an incomplete knowledge of its diversity still hampers a better understanding of its origins and diversification. The fossorial lizard genus Calyptommatus (Gymnophthalmidae) is endemic to sandy habitats of the Caatinga, being currently represented by four allopatric species. In this study, we used morphological and molecular data to assess population-level variation in Calyptommatus. We found a new morphotype of Calyptommatus from the state of Bahia, Brazil, readily distinguished from congeners by the presence of a frontal scale. Morphological, nuDNA and geographic data support the recognition of a new species herein described as Calyptommatus frontalis sp. nov. Nevertheless, genetic data revealed mito-nuclear+morphology discordance, with populations with frontal scales distributed in three distantly related mtDNA clades, suggesting either potential historical and/or current introgressions or incomplete lineage sorting. Further data are needed to clarify the status of the two other mtDNA clades displaying a frontal scale.